Standardized nailfold capillaroscopy in children with rheumatic diseases: a worldwide study. (25th August 2022) - Melsens, Karin; Cutolo, Maurizio; Schonenberg-Meinema, Dieneke; Foeldvari, Ivan; Leone, Maria C; Mostmans, Yora; Badot, Valérie; Cimaz, Rolando; Dehoorne, Joke; Deschepper, Ellen; Frech, Tracy; Hernandez-Zapata, Johanna; et al.
Abstract: Objectives: To standardly assess and describe nailfold videocapillaroscopy (NVC) assessment in children and adolescents with juvenile rheumatic and musculoskeletal diseases (jRMD) vs healthy controls (HCs). Material and methods: In consecutive jRMD children and matched HCs from 13 centres worldwide, 16 NVC images per patient were acquired locally and read centrally per international consensus standard evaluation of the EULAR Study Group on Microcirculation in Rheumatic Diseases. A total of 95 patients with JIA, 22 with JDM, 20 with childhood-onset SLE (cSLE), 13 with juvenile SSc (jSSc), 21 with localized scleroderma (lSc), 18 with MCTD and 20 with primary RP (PRP) were included. NVC differences between juvenile subgroups and HCs were calculated through multivariable regression analysis. Results: A total of 6474 images were assessed from 413 subjects (mean age 12.1 years, 70.9% female). The quantitative NVC characteristics were significantly lower or higher in the following subgroups compared with HCs: for density: lower in jSSc, JDM, MCTD, cSLE and lSc; for dilations: higher in jSSc, MCTD and JDM; for abnormal shapes: higher in JDM and MCTD; for haemorrhages: higher in jSSc, MCTD, JDM and cSLE. The qualitative NVC assessment of JIA, lSc and PRP did not differ from HCs, whereas the cSLE and jSSc, MCTD, JDM and cSLE subgroups showed more non-specific and scleroderma patterns, respectively. Conclusions: This analysis resulted from a pioneering registry of NVC in jRMD. The NVC assessment in jRMD differed significantly from HCs. Future prospective follow-up will further elucidate the role of NVC in jRMD. Graphical Abstract: